Corporate social performance in search of financial meaning: Evidence from Moroccan listed companies - Loubna, OUMARI; AAHD, ASSERRAJI; Ouidad, BENLAMRABET (Edelweiss Applied Science and Technology, 2025)
This paper examines the causal relationship between corporate social responsibility (CSR) and financial performance in Moroccan listed companies. Using a quantitative methodology, the study analyzes whether socially responsible practices can influence firms' financial results. Based on data from 30 firms listed on the Casablanca Stock Exchange over the period 2007–2017, the findings reveal no significant causal link overall, although some context-specific effects may exist. These results highlight the complexity of the CSR–financial performance relationship and emphasize the importance of considering sectoral, temporal, and methodological factors. The research contributes to the literature by providing insights from an emerging market perspective.